Optimalisasi Sistem Presensi Digital Madrasah Melalui Microsoft Excel Dan Qr Code - Rofiuddin Rofiuddin; Indra Maulana; Faizah Kuratul Aini (Lembaga Pengembangan Kinerja Dosen, 2024)
Digitalization is not only developing in companies and public school but is also developing in Madrasah schools such as what happened at Madrasah MA Al-Djufri which is located in the Blumbungan, Pamekasan, based on private schools that currently have minimal use of the system. The service here will provide a website combined with Excel and also the application of QR Codes in implementing daily attendance. The existing opportunities must be used as a spark for enthusiasm to improve and innovate so that they can progress and develop. This activity seeks to provide a solution for private madrasas that do not yet have a website. This service through practical work uses a participatory action research approach. Technically, it is carried out through five stages of competition-based service which include preparation, training, mentoring, competition, and appreciation. The real result of this service activity is the existence of a website in the form of a QR code and Excel to support progress at MA Al-Djufri which previously was still not good. As many as 94% of madrasas stated that in general the implementation of community service activities was carried out very well.